Liquidity and Returns to Target Shareholders in the Market for Corporate Control: Evidence from the US Markets. (25th February 2013) - Lee, Kaun Y.; Chung, Kee H.
Abstract In this paper we analyze how stock market liquidity affects the abnormal return to target firms in mergers and tender offers. We predict that target firms with poorer stock market liquidity receive larger announcement day abnormal returns based on the following considerations. First, target firms with poorer stock market liquidity receive greater liquidity improvements after a merger or tender offer. Second, deals that involve less liquid targets are less anticipated and/or more likely to be completed. Third, less liquid stocks have more diverse reservation prices across shareholders and thus require a higher takeover return. Consistent with these expectations, we show that abnormal returns to target firms' shareholders are significantly and positively related to the difference in liquidity (measured by the bid‐ask spread) between acquirers and targets as well as the magnitude of target firms' liquidity improvement.